INFLUENCE OF DAILY SODIUM INTAKE ON MORTALITY IN HD PATIENTS - Severova, Galina; Karanfilovski, Vlatko; Stojanovska- Severova, Ana; Trajceska, Lada; Dzekova- Vidimliski, Pavlina (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
The aim of our study was to assess the influence of daily sodium intake (DSI) on the cardiovascular mortality in dialysis patients (pts). In prospective, observational study, 156 pts on hemodialysis (HD) were followed for 36 months,until death or kidney transplantation. Cardiovascular (CV) mortality was defined as death resulting from coronary heart disease, sudden death, stroke or complicated peripheral vascular disease and was notified from the patients’ medical history at baseline. Estimated DSI, as a major predictor for CV mortality, was calculated using formula European Best Practice Guidelines (EBPG) on Nutrition. In respect of median DSI (11.7 ± 2.87 g/day) pts were stratified in two groups: Group 1 – pts with low DSI (<11.7 g/day) and Group 2 – patients with high DSI (> 11.7 g/day). The prevalence of CV comorbidities was not significantly different between two groups at baseline. At the end of the study, 41 pts (26.3%) died, among which 24 pts (60%) died from CV diseases. Kaplan-Mayer survival log rank test demonstrated that there was no difference in the cardiovascular survival between HD pts with high DSI and HD pts with low DSI(p>0.05). S erum levels of C-reactive protein (CRP) and mean age were significantly higher in pts diseased from CV disease compared to survived pts. Our results showed that HD pts may be particularly susceptible to non-osmotic sodium accumulation in skin and muscles. This study have shown that there was  no significant influence of baseline DSI on the CV mortality of the pts included in the study. Keywords:   Dietary; mortality; renal dialysis; sodium chloride.   https://doi.org/10.55302/JMS2251054s